Fonti sacre come luoghi di pellegrinaggio nell'Armenia tardo antica e bizantina: i casi studio dei monasteri di Ayrivank/Geghard e Kobayr - Cortese, Arabella (Mitteilungen zur christlichen Archäologie, 2024)
Since the early centuries of the Christian era springs were considered natural elements with a life-giving function. Their water was venerated as holymeans (sometimes associated with the figure of a saint, Christ or the Virgin Mary) and sanctified without door rituals that took place annually. In Armenia, the cult of water had strong pre-Christian roots, archaeological evidence of which is provided by stones called vishaps. With the emergence of Christianity in Late Antiquity, a growing devotion of water at specific natural places spread and these spots became famous pilgrimage sites, often visited by foreign pilgrims attracted by its curative power. Moreover, the sanctity of water also recalled for Armenians their conversion to Christianity, when St. Gregory the Illuminator blessed the water of the river Aratsani to baptize King Tiridates III. Considering the fundamental role that water played for Armenia, the present article aims to investigate the rise, development, and transformation of water cult in two different Armenian pilgrimage sites: Ayrivank/Geghard and Kobayr. Through the analysis of their architectural features, the framing of water and its embedding within the monastic structures, a particular emphasis will be given to understand how the cult of water was staged and what role the natural element might have had in framing the liturgical and devotional space.